Perilaku Seksual Berisiko serta Kaitannya dengan Keyakinan Diri Remaja untuk Mencegah: Studi Deskriptif - Valen Fridolin Simak; Kristamuliana Kristamuliana; Crista Gretasia Sekeon (JURNAL KESEHATAN REPRODUKSI, 2022)
Background: The misuse of media or technology (smartphones, internet) to access various information including pornographic sites can increase adolescents to engage in sexual activity because adolescents continue to feel challenged to do so in real life.Objective: Describe risky sexual behavior and its relation to adolescent self-efficacy to prevent itMethod: The method used in this research is descriptive analytic conducted online by distributing questionnaire links to prospective respondents. The data analysis process used the Pearson testResults and Discussion: There is an increase in the number of incidents of risky sexual behavior, 39% of adolescents are not at risk, 8.1% are low risk, 27.7% are at moderate risk and 25.2% are at high risk. The majority of adolescents have the confidence to prevent risky sexual behavior by 64.8%. Furthermore, the results found that there was a significant relationship between risky sexual behavior and adolescent self- efficacy with a p value of 0.005.Conclusion: The increasing number of cases of risky sexual behavior can be of particular concern for all of us, especially health workers, to be able to develop educational program methods for adolescents, considering that this age is the nation's successor. Keywords: adolescent; risky sexual behavior; self- efficacy